PERANAN KH. ABDUL WAHID HASYIM DALAM PEMERINTAHAN INDONESIA TAHUN (1945-1953) - Agung Syahriman; Agus Mulyana (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2019)
This research entitled “The role of KH. Abdul Wahid Hasyim In Indonesia Administration(1945-1953)”. The research background addressed KH. Abdul Wahid Hasyim figure, whowas the main pioneer in the Religious Ministry during the Unitary State of the Republicof Indonesia. During the Japanese occupation, the Religious Ministry called Shumubu,which was the embryo of the present Religious Ministry. As before independencetook place, KH. Abdul Wahid Hasyim has been heavily involved in several movementorganizations fighting against the occupation in Indonesia. Namely Nahdlatul Ulama(NU), in Majelis Islam A’la Indonesia (MIAI), and also within the Indonesian MuslimShura Council (Masyumi) organization. In additional KH. Abdul Wahid Hasyim wasinvolved in BPUPKI, the Sembilan Committee and PPKI who supported the emergeand the state of Indonesia. After entering the independence period, KH. Abdul WahidHasyim participated in several cabinets and his position once served as a State Minister,Religious Minister of the Republic of Indonesia, and as Religious Minister the UnitaryState of the Republic of Indonesia.